2010
DOI: 10.7124/bc.000143
|View full text |Cite
|
Sign up to set email alerts
|

Expression of lectin and defensin genes in Mironovskaya 808 and Roazon wheat cultivars infected with Pseudocercosporella herpotrichoides

Abstract: The dynamics of expression of protective proteins (lectin and defensin) genes of different genotypes of the winter wheat, affected by P. herpotrichoides, was investigated. Methods. RT-PCR was used for gene expression analysis. Results. We established that the lectin mRNA content in control and infecting plants of the resistant cultivar is considerably higher than in the susceptible one; the character of defensin mRNA accumulation in the investigated cultivars, control and infecting plants, does not change. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…The inoculation was performed under sterile conditions. The cultivation of P. herpotrichoides mycelium was conducted at 25 ± 1 °C for 14 days [4]. …”
Section: Methodsmentioning
confidence: 99%
“…The inoculation was performed under sterile conditions. The cultivation of P. herpotrichoides mycelium was conducted at 25 ± 1 °C for 14 days [4]. …”
Section: Methodsmentioning
confidence: 99%
“…3). Belava et al [2] reported that resistance of plants to pathogens is determined by complicated interdependent systems, which are genetically controlled. The obtained transcripts of the PR-proteins (PR-1.1 and PR-1.2) exhibited a rapid up-regulation as early as 4 days post-inoculation, reached maximum levels after 16 days followed by downregulation after 32 days.…”
Section: The Up-and Down-regulated Genes Obtained By Differential Dismentioning
confidence: 99%
“…3. Вміст СХДГ в проростках пшениці за інфікування P. herpotrichoides Суттєве зниження вмісту сульфоліпідів впродовж експерименту в проростках сорту Roazon (від 81 % до 30 %), може бути зумовлене інтенсивним використанням сульфуру для утворення специфічних пептидів, а саме захисних білків -лектинів та дефенсинів, індукція яких, за отриманими нами попередньо даними [22], відбувається на початку патогенезу та супроводжується накопиченням відповідних мРНК.…”
Section: результати та їх обговоренняunclassified